2017
DOI: 10.1177/1010428317695010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor miR-29c regulates radioresistance in lung cancer cells

Abstract: Radiotherapy is an important treatment option for non-small cell lung carcinoma patients. Despite the appropriate use of radiotherapy, radioresistance is a biological behavior of cancer cells that limits the efficacy of this treatment. Deregulation of microRNAs contributes to the molecular mechanism underlying resistance to radiotherapy in cancer cells. Although the functional roles of microRNAs have been well described in lung cancer, their functional roles in radioresistance are largely unclear. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…MiR-29c pertains to the miR-29 family and has been identified as markedly down-regulated microRNAs in cancer [14,15]. It plays a tumor suppressive role in multiple cancers, such as colorectal cancer [25], lung cancer [26], breast cancer [27], gastric cancer [28], and pancreatic cancer [29]. Our experimental data further confirms this conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…MiR-29c pertains to the miR-29 family and has been identified as markedly down-regulated microRNAs in cancer [14,15]. It plays a tumor suppressive role in multiple cancers, such as colorectal cancer [25], lung cancer [26], breast cancer [27], gastric cancer [28], and pancreatic cancer [29]. Our experimental data further confirms this conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…One of the causes of tumor recurrence and metastasis is that cancer cells acquire radioresistance (RR) during fractionated irradiation (7). It has been reported that RR is acquired in various cancer types, including head and neck cancer, non-small cell lung cancer, breast cancer and PCa (8)(9)(10)(11). RR cells demonstrate resistance to the induction of apoptosis, decreased production of reactive oxygen species (ROS) (12), increased activation of DNA repair (13), and exhibit high migratory and invasive abilities (14).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells acquire RR by fractionated irradiation, and certain features of RR cells have been described (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, to the best of our knowledge, the mechanism underlying RR acquisition during fractionated irradiation is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, it is necessary to detemrine the mechanisms of resistance to radiotherapy. Several studies have demonstrated that tumor recurrence and progression as a consequence of radioresistance can be regulated by microRNAs (miRNAs) (Arechaga‐Ocampo et al ., ; Metheetrairut and Slack, ). miRNAs are master regulators of gene expression; moreover, they have a role in the regulation of carcinogenesis and the control of response to chemo‐ and radiotherapy in breast cancer (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%